2015
DOI: 10.1071/py13176
|View full text |Cite
|
Sign up to set email alerts
|

Consumer satisfaction with practice nursing: a cross-sectional survey in New Zealand general practice

Abstract: An important consideration in health service delivery is ensuring that services meet consumer needs. Whilst nursing services in primary care have grown internationally, there has been limited exploration of consumer satisfaction with these services. This paper reports a descriptive survey that sought to evaluate consumers' perceptions of New Zealand practice nurses (PNs). One thousand, five hundred and five patients who received nursing services at one of 20 participating New Zealand general practices complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The high level of consumer satisfaction with primary care nurse interventions identified in this review is like the wider literature around consumer satisfaction and comfort with nurses in primary care (Bazeley, 2013;Desborough et al, 2015;Halcomb, Davies, et al, 2015;Parkinson & Parker, 2013). Additionally, the finding that there was a level of confusion about the primary care nurses role and scope of practice reflects the broader literature (Halcomb, Peters, & Davies, 2013).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The high level of consumer satisfaction with primary care nurse interventions identified in this review is like the wider literature around consumer satisfaction and comfort with nurses in primary care (Bazeley, 2013;Desborough et al, 2015;Halcomb, Davies, et al, 2015;Parkinson & Parker, 2013). Additionally, the finding that there was a level of confusion about the primary care nurses role and scope of practice reflects the broader literature (Halcomb, Peters, & Davies, 2013).…”
Section: Discussionsupporting
confidence: 55%
“…Consumer satisfaction with a nurse-led model of care is an important, yet poorly understood factor in the evaluation process (Desborough, Phillips, Banfield, Bagheri, & Mills, 2015;Mahomed, St John, & Patterson, 2012). Those consumers who experience positive health encounters are more likely to engage with services, adhere to treatment and enact advice from health professionals (Halcomb, Davies, & Salamonson, 2015;Sofaer & Firminger, 2005). In the light of this, lifestyle interventions that aim to improve health outcomes must be designed and delivered in a way that best reflects the preferences and needs of target individuals (Vogus & McClelland, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This builds on previous research that found that development of rapport (Mahomed et al, 2012) and relationships between nurses and patients (Halcomb et al, 2013) are central to the achievement of patient satisfaction and extending to patient enablement in this model. These partnerships, fostered by adequate time in consultations and continuity of nursing care (Halcomb, Davies, et al, 2014;Mahomed et al, 2012), acknowledge and promote patients' expertise (Hudon et al, 2013).…”
Section: Patients' and Nurses' Behaviours And Interactionsmentioning
confidence: 99%
“…Recognizing the interprofessional nature of general practice, the study of these outcomes in general practice has begun to focus on GPNs. Research approaches have largely been either qualitative (Halcomb, Peters, & Davies, 2013;Mahomed, St John, & Patterson, 2012) or quantitative (Halcomb, Caldwell, Salamonson, & Davidson, 2011;Halcomb, Davies, & Salamonson, 2014;Halcomb, Salamonson, & Cook, 2014). However, general practice is a complex field for research.…”
Section: Introductionmentioning
confidence: 99%
“…Patients' satisfaction with health care is the end result of a complex process, involving a number of factors (Calnan, 1988;Edwards, Staniszweska, & Crighton, 2004;Williams, 1998). In studies in New Zealand and Australia using a 21-item General Practice Nurse Satisfaction Scale, consumers demonstrated a high level of satisfaction with general practice nurses (Halcomb, Caldwell, Salamonson, & Davidson, 2011); those in New Zealand who attended more than 4 visits reported higher levels of satisfaction (Halcomb, Davies, & Salamonson, 2014). Mahomed, St John, & Patterson (2012) described the process of establishing patient satisfaction with nurse-led chronic disease management in general practice.…”
Section: Introductionmentioning
confidence: 98%